Microgravity, Stem Cells, and Cancer: A New Hope for Cancer Treatment - Uğur Topal; Cihan Zamur (Stem Cells International)
Humans are integrated with the environment where they live. Gravitational force plays an important role in shaping the universe, lives, and even cellular biological processes. Research in the last 40 years has shown how exposure to microgravity changes biological processes. Microgravity has been shown to have significant effects on cellular proliferation, invasion, apoptosis, migration, and gene expression, specifically in tumor cells, and these effects may also exist in stem and cancer stem cells. It has also been shown that microgravity changes the effects of chemotherapeutic drugs. Although studies have been carried out in a simulated microgravity environment in cell culture lines, there are few animal experiments or true microgravity studies. Cancer remains one of the most significant problems worldwide. Despite advances in medical science, no definitive strategies have been found for the prevention of cancer formation or to inform treatment. Thus, the microgravity environment is a potential new therapeutic strategy for future cancer treatment. This review will focus on current knowledge on the impact of the microgravity environment on cancer cells, stem cells, and the biological behavior of cancer stem cells.